The Genus Dacryodes Vahl.: Ethnobotany, Phytochemistry and Biological Activities - Leseho Swana; Bienvenu Tsakem; Jacqueline V. Tembu; Rémy B. Teponno; Joy T. Folahan; Jarmo-Charles Kalinski; Alexandros Polyzois; Guy Kamatou; Louis P. Sandjo; Jean Christopher Chamcheu; Xavier Siwe-Noundou (MDPI AG, 2023)
Dacryodes Vahl. species, belonging to the Burseraceae family, are widely used in traditional medicine in tropical regions to treat a range of ailments including malaria, wounds, tonsillitis, and ringworms. This review discusses the distribution, ethnobotanical uses, phytochemistry, and bioactivities of Dacryodes species. The intent is to spur future research into isolating and identifying key active principles, secondary metabolites, and crude extracts, and evaluating their pharmacological and toxicological effects, as well as the mechanism of actions to understand their medicinal benefits. A systematic review of scientific electronic databases from 1963 to 2022 including Scifinder, Scopus, Pubmed, Springer Link, ResearchGate, Ethnobotany Research and Applications, Google Scholar, and ScienceDirect was conducted with a focus on Dacryodes edulis (G.Don) H.J. Lam and Dacryodes rostrata (Blume) H.J. Lam. Pharmacological data revealed that D. edulis isolates contain secondary metabolites and other phytochemical groups belonging to the terpenoids class with anti-microbial, anticancer, antidiabetic, antiinflammatory and hepatoprotective activities, highlighting its pharmacological potential in the therapy or management of diverse cancers, cardiovascular, and neurological diseases. Thus, phytochemicals and standardized extracts from D. edulis could offer safer and cost-effective chemopreventive and chemotherapeutic health benefits/regimen, or as alternative therapeutic remedy for several human diseases. Nevertheless, the therapeutic potential of most of the plants in the genus have not been exhaustively explored with regard to phytochemistry and pharmacology, but mostly complementary approaches lacking rigorous, scientific research-based knowledge. Therefore, the therapeutic potentials of the Dacryodes genus remain largely untapped, and comprehensive research is necessary to fully harness their medicinal properties.